Rapid generation of Shigella flexneri GMMA displaying natural or new and cross-reactive O-Antigens - Gianmarco Gasperini; Maria Michelina Raso; Fabiola Schiavo; Maria Grazia Aruta; Neil Ravenscroft; Barbara Bellich; Paola Cescutti; Francesca Necchi; Rino Rappuoli; Francesca Micoli (npj Vaccines, 2022)
Abstract Generalized modules for membrane antigens (GMMA) are exosomes released from engineered Gram-negative bacteria and represent an attractive vaccine platform for the delivery of the O-Antigen (OAg), recognized as the key target for protective immunity against several pathogens such as Shigella. Shigella is a major cause of disease in Low- and Middle-Income countries and the development of a vaccine needs to deal with its large serotypic diversity. All S. flexneri serotypes, except serotype 6, share a conserved OAg backbone, corresponding to serotype Y. Here, a GMMA-producing S. flexneri scaffold strain displaying the OAg backbone was engineered with different OAg-modifying enzymes, either individually or in combinations. This strategy rapidly yielded GMMA displaying 12 natural serotypes and 16 novel serotypes expressing multiple epitopes combinations that do not occur in nature. Importantly, a candidate GMMA displaying a hybrid OAg elicited broadly cross-bactericidal antibodies against a large panel of S. flexneri serotypes.